Effective passivation for nanocrystalline Si layer/crystalline Si solar cells by use of phosphosilicate glass. (15th July 2018) - Imamura, Kentaro; Onitsuka, Yuya; Kunieda, Shogo; Kobayashi, Hikaru
Highlights: Improvement of surface passivation effect of a nanocrystalline Si layer. Graded band-gap structure of the nanocrystalline Si layer. Carrier separation enhancement by the graded band-gap structure. Abstract: We have investigated the phosphosilicate glass (PSG) passivation effect on electrical characteristics of the <nanocrystalline Si (nc-Si)/crystalline Si> structure fabricated by use of the surface structure chemical transfer (SSCT) method. Cross-sectional SEM measurements show that PSG can penetrate into nano-sized pores of the nc-Si layer. For thick nc-Si layer, e.g., ∼300 nm, however, un-filled nano-sized pores remain in the deep region of the layer. It is founded that complete PSG filling of the nano-sized pores in the nc-Si layer with its thickness less than ∼160 nm greatly improves the effective minority carrier lifetime. The valence band maximum is found to shift toward the lower energy by the SSCT treatment, indicating the band-gap widening of the nc-Si layer. When pores in the nc-Si layer is completely filled with PSG, the effective minority carrier lifetime increases with the thickness of the nc-Si layer, suggesting formation of the graded band-gap structure which can suppress recombination of photo-generated electron-hole pairs.